Estudio de parámetros de calidad y característica sensorial de dos variedades de pitahaya rosa (Hylocereus undatus), pitahaya amarilla (Selenicereus megalanthus) para su aplicación en procesos agroindustriales - Quijije Rendón, Andreina Elizabeth (2021)
The research project aims to study the quality parameters and sensory characteristics of two varieties of pink pitahaya (Hylocereus undatus) and yellow pitahaya (Selenicereus megalanthus) for their application in agro-industrial processes, for which the characterization of both was studied. varieties from three production areas, by making nectars at different concentrations and obtaining freeze-dried pitahaya pulp. For the evaluation of the best treatment, a balance of matter is considered to be able to determine the performance of the dragon fruit varieties, as well as the nectars and the freeze-drying of the fruit, in addition to applying a sensory evaluation. Regarding the development of the research, a physical characterization (diameter, length, and weight) was carried out, as well as bromatological analyzes (ºBrix and pH) prior to the preparation of nectars and the lyophilization process. To determine the difference between the pitahaya varieties, statistical models (experimental designs) were used, using a completely random block ANOVA for the characterization of pitahaya with a factorial arrangement AxBxC with 3 repetitions, for the elaboration of nectars an ANOVA DBCA with arrangement AxB with 3 repetitions, and for the lyophilization process an ANOVA DBCA with factorial arrangement AxB with 3 repetitions. To establish the effects between the treatment levels, a Tukey significance test was applied (p <0.05), the result of the data obtained was analyzed using different statistical packages "INFOSTAT, STATGRAPHICS" and "STATISTICA". Regarding the characterization of the pitahaya varieties, it was possible to conclude that there was a minimum percentage of variation in weight (0.76% -2.15%), diameter (0.24% -0.36%), length (0 , 47% -0.76%), in ºBrix (21.72) and pH (5.51), if it was possible to determine the best results in the variety of red pitahaya with respect to nectars: ºBrix (12, 15), pH (4.25), acidity (0.00038 g / L), absorbance (3.05) and electrical conductivity (1.23 dS / m), in addition to the organoleptic study we establish the best results: pulp ratio : water1: 3. In the freeze-drying process the red dragon fruit + degree of commercial maturity presented the best results, considering: lower% humidity (0.45%) and higher% water loss (78.22%